Current Account Uncertainty and Currency Premia - Della Corte, Pasquale; Krecetovs, Aleksejs (Management Science, 2023)
We empirically study the relationship between currency excess returns and current account uncertainty, measured as forecast dispersion. We find that investment currencies deliver low returns, whereas funding currencies offer a hedge when current account uncertainty is unexpectedly high. Moreover, an increase in current account uncertainty is associated with higher expected future excess returns on investment currencies. This mechanism is consistent with the recent advances in exchange rate theory based on capital flows in imperfect financial markets. This paper was accepted by Gustavo Manso, finance. Funding: A. Krecetovs thanks the Brevan Howard Centre at Imperial College London for financial support. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4949 .